Evaluation of Infection Prevention and Control (IPC) Program Implementation: A Case Study from One of The Private Hospital in Yogyakarta - Hanum Enggar Pradini (Asian Social Work Journal, 2019)
This research conducted at one of the private hospital was a special Type C Hospital in Yogyakarta that will carry out accreditation in 2018. By 2018, SNARS Edition I has applied as a new standard of accreditation. IPC is included in the hospital management standard group, so that the organizing system a good IPC can improve the quality of hospital services. The purpose of this study was to find out the management and implementation of the IPC at this hospital according to SNARS Edition I. This study used qualitative analysis methods with a case study design. The object in this study is the implementation of the IPC program which was assessed by survey and direct observation using the SNARS Edition I assessment instrument. Respondents in this study were 12 people. The results of the study showed that the IPC score was 39,8%. The head of hospital had not implemented IPC managerial activities according to the guidelines. The IPC Team members have not been informed about their roles, the IPC program has not existed yet, and the surveillance record only noted without any further action, not even reported. Case of IDO tends to increase. Only two members of IPC Team (18,18%) received official IPC training. Existing IPC regulations should be revised and completed especially related to risk management of infection, so it will have more impact on improving facilities and infrastructure. IPC program at this hospital has not yet reached the target based on SNARS Edition I. Keywords: Accreditation, Infection Prevention and Control (IPC), IPC Program Implementation, SNARS Edition I